(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The complex origins of borderline personality disorder must be emphasized includes problematic childhood experiences. The condition is thought to be the product which, in accordance with the multifactorial hypothesis of BPD development, is the result of a complicated interaction between environmental and biological factors. Quite the opposite the purpose of this research to investigate biological variables. As a person enters maturity, there is a correlation between with a history of childhood trauma, including sexual or physical abuse, emotional neglect, abandonment, or other forms of abuse. There are also numerous psychotherapeutic approaches utilized in the management of BPD that include psychotherapy, consisting of cognitive behavioral therapy (CBT), schema‐focused therapy (SFT), dialectical behavior therapy (DBT), and pharmacotherapy (O’Connell & Dowling, 2014). The purpose of this meta-analysis was to evaluate the significance of each form of childhood maltreatment (CM) as it contributes to borderline personality disorder (BPD) in adults. Since a meta-analytic approach was used, an additional purpose of the study was to identify possible moderators of type of CM or type of BPD construct that affected the overall effect size estimate for CM.